Sialography: Report of 3 cases - Reddy Sujatha; Rakesh N; Raghav Namita; Devaraju D; Bijjal Shridevi (Wolters Kluwer Medknow Publications, 2009)
Salivary gland examination is an important part of oral examination, especially because of it′s involvement in most of the systemic diseases. Patients most commonly seek medical attention when the major salivary glands like parotid and submandibular gland become enlarged or painful. The various imaging modalities practiced to check the salivary gland disorders include conventional radiography, sialography, ultrasonography, computerized tomography, radionuclide imaging and magnetic resonance imaging. Sialography is one of the oldest imaging procedures and still most commonly practiced, as it is a chair side procedure, simple to perform, and cost effective. We report the role of sialography as an adjuvant in the diagnosis of bacterial sialadenitis and sialadenosis and as a diagnostic and therapeutic aid in a case of juvenile recurrent parotitis.